A Theory of Corporate Scope and Financial Structure - LI, DAVID D.; LI, SHAN (Journal of Finance, 1996)
ABSTRACT We simultaneously address three basic issues regarding the corporation: the optimal scope of operation, the optimal financial structure, and the relationship between these two. The starting point is that financial structure serves as a bonding device on the managers' self‐interest behavior. The effectiveness of this bonding depends on the distribution of the firm's future cash flow, which in turn depends on the firm's scope. Our theory also links the firm's investment decisions to its operation scope. As empirical implications, the theory reconciles the failure of the 1960s U.S. conglomerates with the success of the Japanese Keiretsu .